The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.33369/jeet.5.4.582-593
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Extrovert and Introvert Student’s Achievement in English Conversation Course

Abstract: This research aimed to find out whether there is a significant difference in achievement between extrovert and introvert students in speaking ability in the English Conversation subject for 2nd-semester students of the University of Bengkulu. This research was causal-comparative research. The subject of this research was students at the 2nd semester English Department Study Program of University Bengkulu who has taken the English conversation subject in the academic year 2019/2020. The researcher used a Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…Based on the background of the study, previous studies did not shed light on the differences between the language aptitude of extrovert and introvert Iranian EFL learners to the best of the researcher's knowledge. The results are similar to the findings of Oktriani, Damayanti and Hardiah [37] who discovered whether there was a significant difference in achievement scores amid extrovert and introvert language learners in speaking ability in the English conversation classes. They found that there were no significant differences between introvert and extrovert personalities in English conversation achievement scores.…”
Section: Discussion Of the Findingssupporting
confidence: 89%
“…Based on the background of the study, previous studies did not shed light on the differences between the language aptitude of extrovert and introvert Iranian EFL learners to the best of the researcher's knowledge. The results are similar to the findings of Oktriani, Damayanti and Hardiah [37] who discovered whether there was a significant difference in achievement scores amid extrovert and introvert language learners in speaking ability in the English conversation classes. They found that there were no significant differences between introvert and extrovert personalities in English conversation achievement scores.…”
Section: Discussion Of the Findingssupporting
confidence: 89%
“…A study proved that extroverts outperformed introverts because one of the characteristics shows that they are outgoing in the communication (Gustriani, 2020). However, supporting the study by Rahmadina (2011, as cited in Oktriani et al, 2021), the mean scores result in the present study proves that introverts outperform extroverts, although there is only a slight difference in their mean scores based on their level of self-concept which is not significant. This indicates that both personalities possess an equal possibility of achieving higher English-speaking proficiency.…”
Section: Discussionsupporting
confidence: 83%
“…It proved that there was a difference between the linguistic skill of extroverts and introverts, but it was not significant (Istigfaroh, 2021). Furthermore, another relevant research for secondsemester English Department students also found that students' personality does not affect their speaking score (Oktriani et al, 2021;Nurmayasari & Rahmawati, 2016;Nurzani, 2012). Similarly, other researchers who conducted similar studies revealed that there is no significant relationship that personality traits can predict foreign language aptitude (Samand et al, 2019;Winarsih, 2019;Chen et al, 2015;Sharp, 2008) and also supported that extroverts and introverts students share no statistically significant difference in terms of lowering anxiety level (Kayaoglu, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…This approach, as described by Herwina (2021), acknowledges students' unique learning styles, interests, and experiences, emphasizing the need for teachers to create adaptive learning environments. Prior studies have explored the impact of personality types on students' academic performance, with mixed findings (Khodabandeh, 2021;Oktriani et al, 2021;Boroujeni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%